Organizational culture and the production of scientific knowledge, in masters and doctoral students, at the Faculty of Administrative Sciences (FCA) of the Universidad Nacional Mayor de San Marcos (UNMSM) – Year 2020, Lima-Peru - Manchego Odar, Sara María (2021)
This research identifies the influence of the organizational culture in the performance of the production of scientific knowledge, in masters and doctorates, through a scheme of generational spaces. Considering the statistical method of the census, a total of 391 masters and doctoral students were surveyed-Year 2020. According to the results, we can affirm that the influence of Organizational Culture in the production of scientific knowledge presents an achievement of Good Level in the academic training of masters and doctoral students, for the production of theses.